Tinjauan Anemia pada Remaja Putri : Analisis Faktor Resiko dan Implikasi Kesehatan Jangka Panjang - Siti Naila Sya’bani; Andriyani Andriyani; Nurmalia Lusida (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Anemia is a common health problem among adolescent girls, which can affect their growth and development. Thi study aims to identify factors that influence the occurrence of anemia in adolescent girls. Both biological and environmental factors contribute to anemia. The method used was a comprehensive literature review, by collecting data from various relevant sources including journals and research reports. The result emphasized the importance of knowledge about adolescent girls health, as well as lack of iron consumtion, irregular sleep patterns and long-duration or irregular menstruation, so there is a need for education n each village to reduce the risk of anemia in adolescent girls. The conclusion of this study shows that the impact of anemia affects physical health, quality of life, productivity and social well-being. Addressing anemia should be a priority in public health policy.